Efficacy of Drumstick Leaf and Jamun Seed Powder as Preservative in Chicken Chips - Kasthuri, S.; Mandal , P.K.; Pal, U.K. (Journal of Meat Science, 2017)
The effect of incorporating 1% drumstick leaf powder (DLP), 1% jamun seed powder (JSP) and 0.5% DLP + 0.5% JSP on physico-chemical, sensory and microbiological quality of chicken chips were evaluated during storage at room temperature for a period of 30 days. All the treatment products showed significantly (P<0.05) lower pH values throughout the storage period than control. No significant (P>0.05) differences were observed in TBA and tyrosine values among the products throughout the storage study. Results on sensory evaluation revealed no significant (P>0.05) difference in appearance, flavour, texture, crispiness and acceptability scores between the products and between the storage days. All the products had very good sensory score (above 7 in 8 point hedonic scale) throughout the storage study for all the sensory attributes. Storage had no significant effects on standard plate count (SPC) up to 20 days of storage and on yeast and mould count (YMC) up to 30 days of storage. The functional chicken chips with DLP (1%), JSP (1%) and DLP (0.5%) + JSP (0.5%) could be stored at room temperature for 30 days without any appreciable deterioration in qualities.